Theoretical and Methodological Bases of the Multicriteria Sustainability Assessment of the Regional Socioeconomic Systems Development - SHATALOVA, Olga Ivanovna; NATELNOVA, Natalia Nikolaev; KOBOZEV, Anatoly Kuzmich; KOBOZEV, Mikhail Anatolyevich; VOROBYEVA, Elena Alekseeva; SHEKHOVTSOV, Evgeny Vladimirovich (Journal of Environmental Management and Tourism; Vol 7 No 3 (2016): JEMT Volume VII Issue 3(15) Fall 2016, 2016)
The authors proposed and implemented a method of sustainability assessment of the development of the regional socioeconomic systems in the article, based on a systematic approach and methods of spatial econometrics, which enables the typology of subjects at the meso level, scenario forecasting of the development of the regional systems for the medium term, and coordination of regional development programs. The purpose of the present study is the development of theoretical and methodological basis of determining the sustainability level of regional development, as well as practical testing of the proposed methodology of multicriteria sustainability assessment of the spatial and dynamic development. In the course of the study, the methods have been used such as dialectical, monographic, analytical, systematic, economic and statistic, target-oriented and strategic management. The methodology was tested on the example of regional development indicators of the subjects of the North Caucasus Federal District of the Russian Federation. This methodology opens opportunities for further growth in the studied regions and allows determining the level of sustainability of regional development of the entities of the macro region with great precision. Based on the practical results, the current trends and patterns of the subjects of the North Caucasian Federal District have been identified, and the conclusion can be made on significant differentiation of the components of the test subjects of the Federal District within the allocated areas of study for the entire analyzed period.
Keywords: regional system; methodology; factors of development; algorithm; indicators